A new metaheuristic inspired by gravity waves (MIGW) for finding the shortest path in an urban road network. - Dr. Cheikh MOUILAH , Dr. Mahmoud FAHSI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The shortest path problem in a graph is a concern of a lot of research since the fifties of the last century, in this paper we try to solve this problem with a new metaheuristic inspired by the confrontations of two gravity waves on a liquid surface. The starting point (source) is the center of the first wave, while the destination point (destination) is the center of the second wave. To find the shortest path, this metaheuristic uses four populations which progress in parallel on the urban network, the meetings between its individuals give several optimal routes in both directions (source—destination and destination—source). The parallelism of the progression of these populations and the mutual competition of threads on common resources are the subject of this paper.